Evaluation of the cytotoxic and genotoxic effect of garlic (Allium sativum L.) root cells after exposure to contaminant solution - L. P. N. Ramos; L. S. D. Nascimento; J. S. Lima; C. B. M. Farias; V. S. Mello; I. V. Kasburg (Scientific Electronic Archives, 2020)
Water contamination is much more common than imagined, because it is practically impossible today to have an ecosystem that has not suffered directly or indirectly from humans. Studies with the aim of genotoxicity and mutagenesis use bioindicators as the basis of tests, the most used are from the Allium ssp family. When we mention cytogenetic damage, the intensity depends mainly on the degree of exposure, quantity, chemical nature and of the possible combinations between the contaminants, also influenced by the characteristics and conditions of the environment in which the organisms considered bioindicators are submitted. The present work has the objective of analyzing the cytotoxic, genotoxic and mutagenic effects induced by contaminating material that cause chromosomal alterations by means of mitotic index analysis using as bioindicator Allium sativum (garlic). The experiment was carried out at the Laboratory of Cytogenetics and Culture of Vegetable Tissues at the University of the State of Mato Grosso (UNEMAT) at the Alta Floresta Campus - MT. The soil was collected and stored separately using 200 grams of each sample with three treatments: surface, 20 cm and 40 cm deep, making a tea with 200 ml of distilled water and then measuring the pH. Using a direct method where the bioindicator is submitted directly to the tea solution, awaiting the emission of roots, and the indirect method, where the bioindicator is submitted first, the stimulation of root formation for 72 hours and then is submitted to contaminating solution. The plates readings to observe the interior of the cell using crushing techniques were performed in 24, 48 and 72 hours of experiment (indirect method) and 24 hours (direct method, also measuring the roots). With the results, we can state that the material used as pollutant (soil sample) has a cytotoxic and genotoxic potential in the bioindicator material, presenting high potential in the cell cycle induction, provoking various chromosomal aberrations.